ANALISIS POTENSI KARIR BERDASARKAN BRAIN COLOR TEST - Sarwo Edy Handoyo; Enrita Atlansyah; Erika Prabawati (PROSIDING SERINA, 2021)
Recognizing your potential is very important to win the competition. The purpose of this community service activity (PkM) is to find out the career potential of students at SMAN 8 Tangerang  City, Banten, Indonesia, using a brain color test. The method of implementing this PkM activity uses a written exam. The exam is carried out by doing questions via google form on November 26, 2021. Students who take the XI class test for social science majors. The results of the brain color distribution of students 46% A (office executives, CEOs), 11% B (scientists, researchers, accountants, engineers, lawyers, chemists/physicists), 19% C (creative workers, TV presenters, artists, marketing professionals ), 19% D (entrepreneurs), and 5% mix of AD. Students who fall into the A-D mix category because their personal test scores on several types of brain color are the same. It is recommended for test participants who are included in the A-D mix to do a personal test again to ensure the type of brain color. If the results are still included in the A-D mix, it means that the participant has multiple talents.